LITERATURA, HISTÓRIA E MEMÓRIA EM CARTA À RAINHA LOUCA DE MARIA VALÉRIA REZENDE - Lima, Walquiria de (2021)
For many years, women have had no voice and time in social spaces, but that has been changing. Contemporary Literature presents as a striking feature the removal of silencing those who, over the years, have been marginalized and invisible. Maria Valéria Rezende is an author who, in all her productions, seeks to give a voice to the invisible. In this work, we have as object the book Carta à Rainha Louca, published in 2019. It presents Isabel das Santas Virgens story’s, a poor woman who was arrested accused of creating a clandestine convent and needs to write to Queen Maria I, known as “Mad Queen”, to defend herself against the accusations. For that, Isabel writes letters between 1789 and 1792 presenting her history and, through them, it is possible to understand socio-political aspects of Brazil-Colony. Even though the novel does not have the present time as a backdrop, the author weaves reflections on Brazil of yesterday and today, exposing the condition of women in the colonial period and allows us to reflect on today's society. The main objective of the dissertation is to analyze the condition of Brazilian women in this period through the book, as well as to understand the nuances between literature, history and memory. It is understood that Literature and History have points in common, and literature is widely used by historians to understand the moments of the past. However, Rezende's novel shows the face of literature using History to create its plots. The author created the novel based on a royal letter addressed to Queen Maria I, found in the Arquivos Ultramarinos de Lisboa, in which a poor white woman from Brazil had to defend herself against accusations of creating a clandestine convent. Still, it seeks to understand the literature authored by women. As a theoretical contribution, the dissertation presents Halbwachs (2004), Candau (2011), Agamben (2009) Dalcastagnè (2005, 2012), Zolin (2009), Del Priore (1988, 2019), Perrot (2005, 2007, 2020), Pesavento (1998, 2000, 2003, 2006), Lima (2006), among others.